Preparing of Cornstarch (Zea mays) Bioplastic Using ZnO Metal - Nurwani Hayati; Lazulva Lazulva (Universitas Negeri Medan, 2018)
The manufacture of the bioplastic was done through the mixing process using an aquades solvent with a ratio massa 10 gram and 7 gram cornstarch, 150 mL aquades, 2 Ml glycerol and 0,5 gram ZnO. This study aim to find out physical characteristies (water vapour transmission rate, water content, thickness,biodegradation) and mechanical charateristics (tensile strength, elongasi, modulus young) are made of cornstrach (Zea mays) using ZnO metal. From the test results tensile strength was 2.744-4.018 Mpa, percentage of elongation was 28.4632.383%, modulus young’s was 8.9031026535-14.08617709Mpa, thickness was 0.16-0.29mm, water vapor transmission rate was 0.4329-1.52525g/m2.24 hours, water content was 13.5-14.5%, and biodegradation was 3.7798-7.0346% and 455-809 days.